1987
DOI: 10.1002/prot.340020406
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic peptides corresponding to sequences of snake venom neurotoxins and rabies virus glycoprotein bind to the nicotinic acetylcholine receptor

Abstract: Peptides corresponding to portions of loop 2 of snake venom curare-mimetic neurotoxins and to a structurally similar region of rabies virus glycoprotein were synthesized. Interaction of these peptides with purified Torpedo electric organ acetylcholine receptor was tested by measuring their ability to block the binding of 125I-labeled alpha-bungarotoxin to the receptor. In addition, inhibition of alpha-bungarotoxin binding to a 32-residue synthetic peptide corresponding to positions 173-204 of the alpha-subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0
2

Year Published

1989
1989
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 48 publications
(1 reference statement)
3
54
0
2
Order By: Relevance
“…For instance, Lentz and his colleagues indicated that rabies virus interacts with nicotinic acetylcholine receptor (nAChR) in order to bind mouse diaphragm (Lentz et al, 1982). A few years later, the same research group identified amino acids located between 173 and 204 in the rabies virus glycoprotein as critical sites for this viral-host interaction (Lentz et al, 1987). Pretreatment of dorsal root ganglion primary neurons with monoclonal antibodies raised against α-subunit of nAChR partially reduced their susceptibility to rabies virus infection (Castellanos et al, 1997).…”
Section: Attachment and Host Receptorsmentioning
confidence: 99%
“…For instance, Lentz and his colleagues indicated that rabies virus interacts with nicotinic acetylcholine receptor (nAChR) in order to bind mouse diaphragm (Lentz et al, 1982). A few years later, the same research group identified amino acids located between 173 and 204 in the rabies virus glycoprotein as critical sites for this viral-host interaction (Lentz et al, 1987). Pretreatment of dorsal root ganglion primary neurons with monoclonal antibodies raised against α-subunit of nAChR partially reduced their susceptibility to rabies virus infection (Castellanos et al, 1997).…”
Section: Attachment and Host Receptorsmentioning
confidence: 99%
“…Residues 173-204 of acetylcholine receptor c~-subunit (Lentz et at., 1987) Residues 48, 50, 51, 121-123 of CD4 molecule (Clayton et al, 1988) Residues 37-53 of CD4 molecule (Jameson et al, …”
Section: )mentioning
confidence: 99%
“…The efficacy of both active and passive immunization is likely to be affected by antigenic differences between viruses. The lyssavirus trimeric glycoprotein is the primary surface antigen, the major target for neutralizing antibodies (8), and is involved in cell binding and entry (34,36,53). Antigenic sites on the glycoprotein have been described using monoclonal antibody escape mutants (8,16,47,51).…”
mentioning
confidence: 99%